GP147 Lost in the scenario: losing sight of the patient when using a structured prescription chart. (June 2019) - Bell, Alison; Dornan, Tim; Conn, Richard
Abstract : Background: Insulin is a dangerous medication and prescribing errors associated with its use can have life-threatening consequences. Holistic prescribing requires involvement of the patient and their family in the process as well as prescribing the medication safely. An insulin prescribing chart structures the task of prescribing insulin but there is a lack of research on its impact on the doctor's behaviour. Aim: To explore how a prescription chart structures the task of prescribing insulin Methods: Qualitative study involving interviews with seven doctors who routinely prescribe insulin for children. Two phase interview: phase one 'free association' interview where doctors described their approach to insulin prescribing; and simulated prescribing task using 'think-aloud' methodology, where doctors verbalised their reasoning while completing an insulin prescription. Interview transcripts were thematically analysed, guided by existing published prescribing frameworks. Doctors' approaches during each interview phase were compared, supported by content analysis of coded data. Results: The introduction of the prescription chart changed the behaviour of doctors while prescribing. Their behaviour moved from a holistic approach to a much narrower, task focused approach to prescribing. Fewer doctors verbalised any intent to interact with the patient while prescribing for them and checked fewer aspects of their prescription when presented with the chart. They moved from a holistic approach to a goal orientated one. Conclusion: This study has shown that the use of a prescribing chart changes doctors' behaviours. Training doctors to use prescribing charts in isolation may de-emphasise the importance of patient engagement. We recommend patient centred prescribing education for medical students and doctors. This may involve a staged progression from prescribing in the classroom setting, to prescribing with a simulated patient, to opportunities to prescribe in the clinical context with supervision.